Effects of 6-Hydroxykaempferol: A Potential Natural Product for Amelioration of Tendon Impairment - Mok, Tsz Ngai; He, Qiyu; Zhang, Xiaoxi; Sin, Tat Hang; Wang, Huajun; Hou, Huige; Pan, Jinghua; Zheng, Xiaofei; Zha, Zhengang; Li, Jieruo (Frontiers in Pharmacology, 2022)
Tendon impairment is a common injury associated with impairment of range of motion and pain. Currently, evidence has confirmed that natural herbs contribute to orthopedics and have shown excellent results in the clinical management of tendon impairment. Shujin Huoxue tablet (SHT) and its complex prescriptions are regularly used in tendon rupture therapy with positive results. This study aimed to discover the potential molecules that promote tendon healing. The Chinese Traditional Medicine System Pharmacological Database Analysis Platform (TCMSP) is the primary resource. The Traditional Chinese Medicine Integrated Database and Encyclopedia of Traditional Chinese Medicine databases were used as secondary databases. The GeneCards database was used to search for reported tendinopathy-related genes by keywords. Functions of the targeted genes were analyzed using Gene Ontology enrichment analysis and Kyoto Encyclopedia of Genes and Genomes. Protein–protein interaction information was extracted from the STRING database. Docking study, MTT assay, quantitative real-time PCR, and migration assays were performed to obtain a better understanding of the herbs according to cell function to test the basic pharmacological action in vitro. A total of 104 disease nodes, 496 target gene nodes, 35 ingredient nodes, and one drug node were extracted. According to the TCMSP database, 6-hydroxykaempferol, which reportedly promotes the proliferation of microvascular endothelial cells, is a molecule found in SHT. We found that it promoted the proliferation and migration of tendon fibroblasts and elevated tendon repair-related gene expression. Purified 6-hydroxykaempferol promoted the proliferation and migration of tendon fibroblasts and increased their mRNA expression in tendon proliferation.